2016
DOI: 10.1111/jfr3.12277
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐optimal design of river dikes using probabilistic methods

Abstract: Given the large investments in dike construction and reinforcements, optimisation of these interventions could contribute to significant cost savings. In this study, a probabilistic method is developed for obtaining the geometry of a river dike cross‐section that fulfils a specified target reliability at a minimal cost. The method takes into account multiple relevant failure mechanisms and various geometric parameters of the dike. Large numbers of cross‐sections are generated and the reliability for each secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Our analysis considers overtopping to account for 100% of the total probability of failure and serves to provide an upper bound on the system reliability ( Figure 4). We confirmed that our results are not significantly altered by prescribing overtopping to account for 60% or 80% of the total probability of failure, which is representative of the plausible range of failure modes (Bischiniotis et al, 2016) (see Figures S2 and S3). A more detailed probabilistic treatment of the different failure modes outlined here, as well as pumping system or floodgate failure, is beyond the scope of this study.…”
Section: Discussion and Caveatssupporting
confidence: 83%
See 1 more Smart Citation
“…Our analysis considers overtopping to account for 100% of the total probability of failure and serves to provide an upper bound on the system reliability ( Figure 4). We confirmed that our results are not significantly altered by prescribing overtopping to account for 60% or 80% of the total probability of failure, which is representative of the plausible range of failure modes (Bischiniotis et al, 2016) (see Figures S2 and S3). A more detailed probabilistic treatment of the different failure modes outlined here, as well as pumping system or floodgate failure, is beyond the scope of this study.…”
Section: Discussion and Caveatssupporting
confidence: 83%
“…Optimal levee designs indicate that the relative contributions of overtopping versus piping or slope instability failures to the total levee failure probability vary depending on site-specific properties, but overtopping is the dominant failure mode (Johnson et al, 2013;Bischiniotis et al, 2016). Our analysis considers overtopping to account for 100% of the total probability of failure and serves to provide an upper bound on the system reliability ( Figure 4).…”
Section: Discussion and Caveatsmentioning
confidence: 99%
“…Macro stability is calculated within the program D-Geo Stability (Brinkman and Nuttall, 2018) with the stability method by Van (2001) and ground water model by TAW (2004). The method by Van (2001), like the Bishop (1955) method, calculates the sum of the driving moments (S) and the total resisting moment (R) along the slip plane. However, it also accounts for uplift forces on the interface of aquifers present beneath most dikes.…”
Section: Multifunctionalmentioning
confidence: 99%
“…The stability of the slope is calculated with the method by Van (2001) for the slip plane and works on the same principle as the method by Bishop (1955). The main difference between the methods is the separation of the slip plane in an active circle connected by a straight section followed by a passive circle.…”
Section: Appendix D: Macro Stability Limit State Functionmentioning
confidence: 99%
“…For instance, stability of embankment and infrastructure is often influenced by drying-wetting condition during water level fluctuation. Piping phenomenon, as one of the cause of river embankment failure, is induced by the water-level difference between the inner and the outer part of the river embankment, and failure happens when the resisting moment becomes lower than the driving moment (Bischiniotis et al, 2016). In detail, piping induced by the rapid draw down phenomenon and high water level during rainy season affects the worst piping effect.…”
Section: Introductionmentioning
confidence: 99%